Pengaruh Konsumsi Energi dan Deforestasi Terhadap Output Nasional Lima Negara Anggota ASEAN - Neni Kristiana; Lorentino Togar Laut; Jalu Aji Prakoso (Fakultas Ekonomi dan Bisnis Universitas Lampung, 2021)
The economic development aimed at improving people’s welfare often ignores the negative impact of the surrounding environment. The high use of energy aimed to increase the national income of the five ASEAN members hurts the environment by increasing CO2 levels in the air. This research aims to analyze the effect of CO2 emissions, coal consumption, electricity consumption and deforestation on national output in five ASEAN members. The variable used in this research is national output as the dependent variable and CO2 emissions, coal consumption, electricity consumption and deforestation as the independent variables. This research uses secondary data. The data is the panel data of five ASEAN members (Indonesia, Malaysia, Thailand, Philippines, Myanmar) from 2002 until 2018. The research method in this time is panel data regression, using Fixed Effect Model. This research shows that in five ASEAN members from 2002 until 2018, CO2 emissions harm national output, coal consumption, and electricity consumption positively affects national outcome, while deforestation does not affect national output.